Can financial performance affect firm value?: mediated by dividend policy - Nurfala Safitri; Dinnul Alfian Akbar; Sri Delasmi Jayanti (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
This study aims to discover the effect of liquidity on firm value with dividend policy as the intervening variable in the manufacturing companies indexed by ISSI in the period of 2014-2018. In this study, we used 10 companies as samples. This study used quantitative research method. As for sampling technique, we used purposive sampling. The type of data is secondary data. Data analysis techniques used in this study were descriptive data analysis, classical assumption test analysis, multiple linear regression, whilst research hypotheses were tested by Eviews 9. The results showed that dividend policy did not mediate solvability effect on firm value, however dividend policy mediated the effect of liquidity on firm value.